Environmental taxes and renewable energy consumption nexus: Role of environmental governance and technological innovation - Kanchan Kumar Sen; Shahadat Hosan; Shamal Chandra Karmaker; Andrew J Chapman; Bidyut Baran Saha (Sustainable Futures)
The effectiveness of environmental taxes in promoting renewable energy consumption (REC) depends on strong institutional and technological support. This study investigates how environmental taxes influence REC in OECD nations, emphasizing the mediating roles of environmental governance and environmental-related technological innovation. Econometric analyses reveal that taxes alone have a limited impact on REC, but their effectiveness increases significantly when reinforced by robust governance and innovation. Findings highlight the need for an integrated policy framework where taxation, governance, and innovation work together to accelerate the clean energy transition. These insights offer valuable guidance for achieving SDG 7 and advancing sustainable energy policies.